Pengaruh Kondisi Lingkungan, Perilaku Berbagi Pengetahuan, Proses Perencanaan Strategis, terhadap Inovasi dan Kinerja (Studi pada UKM Sentra Kerajinan Kulit di Jawa Timur) - Rofiaty -; MS Idrus; Ubud Salim; Christantius Dwiatmadja (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research is to integrate causality model between environment, knowledge sharing behavior, and strategic planning process, to innovation and performance. The sample of the research is small and medium sized enterprise of handicraft industry that made of leather, e.g. shoes, leather jackets, bags, luggage, belts, wallets, and other products made of genuine leather which still can’t compete in East Java. Structural Equation Modelling is used to process the data. The result shows that from the nine tested hypotheses, there are 7 (seven) accepted tests (and they have significant impact), and there are 2 (two) unaccepted tests (and they have insignificant impact), such as the impact of environment and knowledge sharing behavior to business performance. The findings of this research are, first, the impact of sharing behavior/developing knowledge to work performance of small and medium sized enterprise should use innovation as antecedent variable, and second, the impact of environment changes to work performance of small and medium sized enterprise is determined by strategic planning variable mediation. A stronger work environment changes force the enterprises to create effective strategic planning process intensity, which do some sustainable information search about market and other information to create creativity in product making designing and services. The implementation of small and medium sized enterprise’s knowledge management is not only just to share knowledge about their market, but also must be followed by increasing the knowledge/ability of the employers, giving opinion about employers’ performance, fluently communicating, and using technology to design product and facilitate communication. New idea in this research is knowledge sharing behavior at SMEs, which have a significan role to create innovation and creativity to enhacing performance.Keywords: Environment, Knowledge Sharing Behavior, Strategic Planning Process, Innovation, and Performance.